The Influence of Work-Life Balance and Organizational Citizenship Behavior (OCB) on Employees Performance at PT. Air Minum Bandarmasih (PERSERODA) Banjarmasin - Karlina, Iin; Prima Jaya, Fanlia (PT. Hanken Sukses Jaya, 2025)
Employee performance is an important element in supporting the operational effectiveness of a company, including in the public service sector such as PT. Air Minum Bandarmasih (PERSERODA) Banjarmasin. Although the performance achievements in the 2023 fiscal year were classified as “good,” several operational aspects still did not achieve maximum scores, particularly in terms of work efficiency and timeliness. This study aims to analyze the influence of Work Life Balance and Organizational Citizenship Behavior (OCB) on employee performance, both partially and simultaneously. This study uses a quantitative approach with a survey method. A total of 100 respondents were selected using the Proportional Stratified Random Sampling technique. The research instrument was a questionnaire that had been tested for validity and reliability. Data analysis was performed using multiple linear regression using SPSS software. The results showed that Work Life Balance had a positive and significant effect on employee performance, with the dominant dimension being Satisfaction Balance. Organizational Citizenship Behavior (OCB) also has a positive and significant effect on employee performance, with the most prominent dimension being helpfulness (Altruism). Simultaneously, both variables contribute 23.3% to the improvement in employee performance, while the rest is influenced by other factors outside the research model. These findings indicate the importance of strengthening Work Life Balance policies.